2016
DOI: 10.1007/s00535-016-1281-2
|View full text |Cite
|
Sign up to set email alerts
|

Oral branched-chain amino acid granules improve structure and function of human serum albumin in cirrhotic patients

Abstract: Background and aimsThe aim of this study was to evaluate structural and functional alterations of human serum albumin (HSA), with a special focus on the oxidized and reduced forms, in patients with chronic liver disease. We also investigated whether oral branched-chain amino acid (BCAA) supplementation could induce structural changes and improve the functions of HSA.MethodsThe proportion of reduced and oxidized HSA was determined in 16 healthy controls and in 20 chronic hepatitis and 100 cirrhotic patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 39 publications
1
40
1
1
Order By: Relevance
“…Furthermore, the knockdown of DsbA‐L in Caenorhabditis elegans resulted in a significant decrease in the respiration rate and a change in the fatty acid metabolism in mitochondria . The redox state of HSA has been proposed as a plasma marker of chronic oxidative stress‐related diseases, including the progression of chronic hepatitis and cirrhosis . The results of this study showed that the oxidized HSA level was increased in subjects who were overweight and/or with NAFLD ( Supplementary Figure S2 ).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Furthermore, the knockdown of DsbA‐L in Caenorhabditis elegans resulted in a significant decrease in the respiration rate and a change in the fatty acid metabolism in mitochondria . The redox state of HSA has been proposed as a plasma marker of chronic oxidative stress‐related diseases, including the progression of chronic hepatitis and cirrhosis . The results of this study showed that the oxidized HSA level was increased in subjects who were overweight and/or with NAFLD ( Supplementary Figure S2 ).…”
Section: Discussionmentioning
confidence: 74%
“…The redox state of human serum albumin (HSA) was used as a systemic oxidative stress marker, as it reflects the progression of oxidative stress‐related chronic diseases . The redox state of HSA was analyzed by high‐performance liquid chromatography for the fasting serum samples that were collected at the end point of the observation period, as described in a previous study for assessing the level of oxidative stress .…”
Section: Methodsmentioning
confidence: 99%
“…Although several modes of actions, including reduction of angiogenesis and promotion of insulin-dependent hepatocyte proliferation, have been proposed for BCAA's beneficial effects in chronic liver diseases, one of the most important action of BCAA is the promotion of ALB synthesis by oxidative-stress-reducing and oxidized-albumin-lowering actions [30,31] . In addition, it has been recently reported that oral administration of BCAAs leads to the inhibition of hepatocarcinogenesis through the synthesis of ALB and the reduction in the oxidative stress level [32] . In this study, we identified serum ALB level <4.0 as the strongest risk factor for HCC development in patients with HCV-related liver diseases.…”
Section: Discussionmentioning
confidence: 99%
“…HSA is chemically classified into two main forms based on the redox state: human non‐mercaptalbumin (HNA; oxidized form) and human mercaptalbumin (HMA; reduced form; Fig. ) . Additionally, HNA is subclassified into two different states according to cysteine‐34 modification: HNA‐1, which is reversibly oxidized, and HNA‐2, which is highly oxidized .…”
Section: Introductionmentioning
confidence: 99%
“…) . Additionally, HNA is subclassified into two different states according to cysteine‐34 modification: HNA‐1, which is reversibly oxidized, and HNA‐2, which is highly oxidized . Under oxidative stress, HMA changes into HNA by buffering reactive oxidative species; therefore, the fraction of HMA in HSA (f[HMA]) has been considered a biomarker that reflects the redox state in the human body …”
Section: Introductionmentioning
confidence: 99%